Thermal Conductivity of Graphitic Carbon Nitride Nanotubes: A Molecular Dynamics Study - Hui Guo; Chunqing Huo; Liang Yang; Shiwei Lin (Advances in Condensed Matter Physics)
Graphitic carbon nitride (g-C3N4) nanotubes are recently gaining increasing interest due to their extraordinary physicochemical properties. In the following, we report on simulations using a method of nonequilibrium molecular dynamics and focus on the thermal conductivity variation of g-C3N4 nanotubes with respect to different temperatures, diameters, and chiral angles. In spite of the variation of diameters and chiral angles, the structure of nanotubes possesses high stability in the temperature range from 200 K to 600 K. Although there is little change of the thermal conductivity per unit arc length for nanotubes with the same diameter at different temperatures, it decreases significantly with increasing diameters at the same temperature. The thermal conductivity at different chiral angles has little to do with how temperature changes. Simulation results show that the vibrational density of states of nanotubes distributed, respectively, at ∼11 THz and ∼32 THz, indicating that heat in nanotubes is mostly carried by phonons with frequencies lower than 10 THz.